The Effectiveness of Interactive E-Modules on Physics Concept Understanding in the Implementation of the Merdeka Curriculum: A Literature Review - Maria Anastasia Da Lopez; Ziadatun Nikmatillah; Alia Cahyani; Gunawan Gunawan; Nina Nisrina (Indonesian Publication Center, 2026)
Technological advancements in education have driven the use of more interactive digital teaching materials, one of which is the e-module. In physics learning, which is inherently abstract, students' conceptual understanding remains a significant challenge. Along with the implementation of the Merdeka Curriculum, which emphasizes independent and technology-based learning, innovative learning media are required to enhance student engagement and comprehension. This study aims to analyze the effectiveness and characteristics of interactive e-modules on students' conceptual understanding of physics, one of which is on wave mechanics. The method employed is a literature review, analyzing a number of relevant scientific articles obtained from the Google Scholar database using the Publish or Perish application based on specific criteria. The results of the study indicate that interactive e-modules are generally equipped with features such as animations, simulations, and quizzes, which can increase student engagement in the learning process. Furthermore, the use of interactive e-modules also shows a positive trend toward improving students' conceptual understanding and learning outcomes. Therefore, interactive e-modules hold great potential to support more effective and innovative physics learning within the implementation of the Merdeka Curriculum.